Covid run game serious game for health : Covid-19 preventive care - Mohd Azrul Hisham, Mohd Adib; Muhammad Nor Hakim, Hassan (2021)
Since 12th December 2019 , COVID-19 has increasingly spread throughout the world rapidly and the situation is very worrying. They are less aware about the dangerous of COVID-19. Malaysian community fewer preventive information and knowledge, which educate and give awareness about the dangerous of COVID-19